Peripheral analgesic effect of a novel curcuminoid derivative: possible involvement of peripheral opioid receptor and ATP-sensitive potassium ion channel - Lee, Ming Tatt; Ho, Yu Cheng; Tham, Chau Ling; Akira, Ahmad; Lajis, Nordin; Ahmad Israf, Daud; Sulaiman, Mohd Roslan (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Background/Objectives: The present study investigated the local analgesic effect of a novel synthetic cyclohexanone derivative, 2,6-bis-4-(hydroxyl-3-methoxybenzilidine)-cyclohexanone, or BHMC, in a mouse model of peripheral nociception. Methods: Local administration of BHMC (0.5–60 µg/paw) intra-plantarly in the hindpaws of mice exhibited significant inhibition in carrageenan-induced paw hyperalgesia. Intra-plantar pretreatment of naloxone (non-selective opioid receptor blocker), D-Phe-Cys-Tyr-D-Trp-Orn-Thr-Pen-ThrNH2 (CTOP, selective µ-opioid receptor blocker), and nor-binaltorphimine (nor-BNI, selective κ-opioid receptor blocker), but not naltrindole hydrochloride (selective δ-opioid receptor blocker), reversed the anti-nociceptive effect of BHMC. The peripheral analgesic effect of BHMC was also reversed by intra-plantar pretreatment of methylene blue (soluble guanosyl cyclase blocker), but not NG-nitro-L-arginine (L-NAME, nitric oxide synthase blocker). Involvement of the potassium channel in the local analgesic effect of BHMC was shown through the reversed analgesic effect by intra-plantar pretreatment of glibenclamide (ATP-sensitive potassium channel blocker), but not by charybdotoxin (large-conductance calcium-sensitive potassium channel blocker), apamin (small-conductance calcium-sensitive potassium ion channel blocker), or tetraethylammonium (voltage-sensitive potassium channel blocker). Results: Taken together, the present study demonstrated that the local administration of BHMC attenuated nociception, with possible mechanisms that may involve the desensitization of inflammatory mediators’ receptors, opioid receptor activation, and nitric oxide-independent cyclic guanosine monophosphate activation of ATP-sensitive potassium ion channel opening. Conclusions: The current findings may further support the exploration of BHMC as a new therapeutic agent for pain and inflammation, for the betterment of human health.